Foraminiferal and Palynological Records of an Abrupt Environmental Change at the Badenian/Sarmatian Boundary (Middle Miocene): A Case Study in Northeastern Central Paratethys - Danuta Peryt; Przemysław Gedl; Elżbieta Worobiec; Grzegorz Worobiec; Tadeusz Marek Peryt (Geosciences, 2024)
The Badenian/Sarmatian boundary in the Central Paratethyan basins is characterised by a change from open marine conditions during the late Badenian to the assumed brackish conditions during the early Sarmatian. The foraminiferal and palynological results of the Badenian/Sarmatian boundary interval in the Babczyn 2 borehole (in SE Poland) showed that the studied interval accumulated under variable, unstable sedimentary conditions. The Badenian/Sarmatian boundary, as correlated with a sudden extinction of stenohaline foraminifera, is interpreted as being due to the shallowing of the basin. The lack of foraminifera and marine palynomorphs just above the Badenian/Sarmatian boundary can reflect short-term anoxia. The composition of the euryhaline assemblages, characteristic for the lower Sarmatian part of the studied succession, indicates from marine to hypersaline conditions.